A standardised pre-hospital electronic patient care system. (11th November 2009) - Gaynor, Mark; Myung, Dan; Gupta, Amar; Moulton, Steve
This paper describes the design, development and testing of a pre-hospital documentation and patient monitoring application called iRevive. The application utilises a sensor gateway and data mediator to enable semantic interoperability with a wide variety of medical devices and applications. Initial test results indicate that complete and consistent pre-hospital Electronic Medical Records (EMR) can be semantically exchanged with two heterogeneous, in-hospital IT applications.